Pengaruh Kualitas Produk, Persepsi Harga Dan Promosi Terhadap Keputusan Pembelian Produk Hijoo Salad - Atmah, Thursina Hafsatu; Tarigan, Hairani (Universitas Pahlawan Tuanku Tambusai, 2024)
There is intense competition from similar business actors, it is a must to present products with superior quality standards, affordable prices, and effective promotional strategies. The purpose of this study is to determine whether there is an influence of product quality, price and promotion on the purchase decision of Hijoo Salad products. The method used in this study is a quantitative method by collecting respondents' responses through direct surveys in the form of questionnaires. The results of this study found that product quality, price perception and promotion together influence the purchasing decisions of Hijoo Salad consumers in Setiabudi. Other factors not studied in the study may also have influenced purchasing decisions. Based on the results of this study, the authors recommend several suggestions for PT. Hijoo Royo - Royo, which is to increase promotions to make them more attractive to consumers, improve the quality of products offered and be able to determine prices well. This research is expected to help Hijoo Salad in increasing customer satisfaction and developing better products.